Alterações epigenéticas induzidas pelo IFN-y e envolvidas na diferenciação de células dendríticas derivadas de monócitos (Mo-DCs) durante a malária - Fernanda Chacon Cavalcante (2018)
In infectious diseases such as malaria, monocytes, macrophages and dendritic cells are cellular populations that have crucial role in tissue repair, detection of presence of invading micro-organisms, initiating protective immune responses. Inflammatory and microbial stimuli can lead to the differentiation of monocytes in dendritic cells (Mo-DCs) in the inflammatory site. During experimental cerebral malaria (ECM), Mo-DCs are differentiated in response to inflammatory mediators, such as IFN-, and have key role in developing neurological symptoms observed in experimental brain malaria. Is not well known about epigenetic factors induced by infectious diseases, especially in malaria. Given the importance of the Mo-DCs in the imunopathogenese of cerebral malaria and other infectious diseases in this work, the possible mechanisms epigenetic involved in the differentiation of MO-DCs were evaluated. Moreover, being IFN- a key cytokine for the diferentiation of these cells, we also evaluate their role as epigenetic regulator of this process. For this, Mo-DCs and monocytes were purified from the spleen and bone marrow of animals WT and IFN--/- for the analysis of the gene expression of enzymes involved in the epigenetic regulation. On one hand, studied demonstrated that the enzyme methyltransferase Kmt2c (MLL3) was highly expressed in Mo-DCs of the spleen in a dependent manner on IFN-. On the other hand, the enzyme methyltransferase Ezh2, responsible for the repression of the transcription, was highly expressed in the absence of IFN-. These findings suggest that these enzymes may be involved in regulating the transcription of essential genes for the differentiation of Mo-DCs in the spleen during the infection by P.b. ANKA. More studies are needed to identify the target genes involved with these epigenetic mechanisms and what the effects of inhibition of these enzymes in malaria. Finally, Kmt2c and Ezh2 may represent important targets for the development of new therapies for the treatment of brain malaria.